Beyond Bilingualism Multilingualism and Multilingual Education (Multilingual Matters, 1998)
This book provides theoretical, empirical and practical bases for planning and implementing multilingual education programmes that prepare students for a multilingual world. It addresses the unique challenge that promoting multilingualism and multilingual education presents